Does Foreign Investors’ Information Access Vary with Geopolitical Tensions? Evidence from Corporate Conference Calls - LU, YIFEI; WU, JOANNA SHUANG; YANG, YUCHENG (JOHN) (Journal of Accounting Research, 2026)
ABSTRACT We study how foreign investors’ access to corporate information varies with pairwise geopolitical tensions between the investor's and investee's countries. Using a sample of 1,760 country‐pairs, we find that geopolitical tensions between a conference call host firm's country and a foreign country relate negatively with investor participation from that foreign country as well as the quality and tone of management responses in the call, suggesting reduced foreign investor information access with rising tensions. A single‐country analysis of Chinese AB‐share firms produces similar inferences. With higher China–foreign tensions, foreign attendance at private meetings with management declines, and English translations of local language disclosures become less frequent and shorter in length. Curtailment in English translations is more pronounced when local language disclosures contain politically sensitive words, suggesting lower information supply by firm choice. Reduced disclosures from geopolitical tensions are impounded in foreign investors’ asset pricing decisions, resulting in steeper foreign‐share price discounts.